Effects of Single-Dose Prucalopride on Intestinal Hypomotility in Horses: Preliminary Observations - Laus, Fulvio (Sci Rep, 2017)
Abnormalities of gastrointestinal motility are often a challenge in horses; however, the use of prokinetic drugs in such conditions must be firmly established yet. For this reason we carried out a preliminary study on the effects of prucalopride on intestinal motor activity of horses with gut hypomotility. The effect of prucalopride per os by oral dose syringe (2 mg/100 kg body weight) was assessed by abdominal ultrasound (evaluating duodenal, cecal, and colonic motor activity) in six horses with gut hypomotility. After administration of prucalopride, a significant increase of contractile activity was found in the duodenum at 30 minutes (p = 0.0005), 60 minutes (p = 0.01) and 90 minutes (p = 0.01), whereas in the cecum and in the left colon the increase was only present at 60 minutes (p = 0.03, and p = 0.02, respectively). No changes from baseline heart and respiratory rate or behavior side effects were observed after administration of the drug and throughout the observation period. Prucalopride may be a useful adjunct to the therapeutic armamentary for treating hypomotile upper gut conditions of horses. Dosing information is however needed to establish its actual clinical efficacy and its proper effects on the large bowel in these animals.